Digital protection and monitoring system for medium voltage substations and electric installations - Lane, V.E; Joly, J.M (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
A new approach to substation control and protection, aimed at the improvement of the management of power networks and substations, is being advocated by manufacturers and adopted by increasing numbers of power supply authorities. Protection, substation local control, operator interfaces, communication, remote control and a host of monitoring functions, most of which were previously segregated and device-oriented, with discrete relays or modules for each function, are now being integrated into multi-function microprocessor based units and interconnected on various types of local area networks. So, every component communicates to each other, sharing information through the local area network, and systems are smaller, because only one sensor is necessary for each information, instead of one sensor per component as before. The report defines the notion of a "target architecture" that manufacturers should focus on as far as interoperability is concerned in protection and monitoring control systems for electric substations. It presents a model of an integrated digital system that might provide the answer. This model is currently available and is well adapted to medium voltage electrical installations in industrial networks. (2 pages)